Hacia una perspectiva ampliada de la historia de la literatura policial en la Argentina: ¡Estafen! y Caterva de Juan Filloy y los usos del género negro - Guevara, Martina (2019)
Th e purpose of this article is to demonstrate that the novels ¡Estafen! and Caterva by Juan Filloy are permitted to be read as noir novels. Th is aﬃ rmationnot only seeks to diﬀ erentiate itself from a literary critical production that chose to read Filloy only as a atipycal writer, but also it aims to discuss crystallized constructions about the origins of the detective genre in Argentina. By doing it this way, our interpretation of this two novels put into tension both thecanonical conception that situates the beginning of the detective genre in the 1940s and also the idea that the fi rst manifestations of the noir novel began at the end of the 1960s.